2022
DOI: 10.30550/j.lil/2022.59.s/2022.08.16
|View full text |Cite
|
Sign up to set email alerts
|

New Species and Combinations in the Cerrenaceae (Polyporales, Basidiomycota)

Abstract: The classification and taxonomy of the Polyporales have undergone tremendous change and made significant progress in the last ten years. A case in point is the Cerrenaceae that was created just five years earlier. This is one of the smaller, lesser-known families with just five recognized genera and is well-defined and supported by phylogenetic analyses but difficult to characterize by morphology. Some genera and species in the Cerrenaceae display a range in basidiome habit, hymenophore configuration, and hyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The phylogenetic position of Meripilus (i.e., whether this genus is truly nested in the Physisporinus clade or not) has not been confirmed by multigene phylogenetic analyses with sufficient sequences yet, although this study showed that, unlike Physisporinus, Meripilus species do not produce acanthophyses. In the Cerrenaceae, Polyporales group, a taxonomic problem regarding the "R. hypobrunneus"/"R. vinctus" clade, which was also pointed out by Nakasone and Ortiz-Santana (2022), was more clearly highlighted by our phylogenetic analysis (Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 62%
“…The phylogenetic position of Meripilus (i.e., whether this genus is truly nested in the Physisporinus clade or not) has not been confirmed by multigene phylogenetic analyses with sufficient sequences yet, although this study showed that, unlike Physisporinus, Meripilus species do not produce acanthophyses. In the Cerrenaceae, Polyporales group, a taxonomic problem regarding the "R. hypobrunneus"/"R. vinctus" clade, which was also pointed out by Nakasone and Ortiz-Santana (2022), was more clearly highlighted by our phylogenetic analysis (Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 62%